JURIDICAL REVIEW OF LAW NO. 21 OF 2007 ON THE PROTECTION AND ERADICATION OF HUMAN TRAFFICKING AS A TRANSNATIONAL HUMAN RIGHTS VIOLATION IN INDONESIA - Ramadhani, Solibah; Novianti, Vera; Murti, Krisna (Faculty of Law Sriwijaya University, 2025)
Human Trafficking (TPPO) is a structured and systematic form of crime that violates human rights as the inherent rights of human beings as creations of God Almighty. This crime not only occurs in Indonesia but has also become a transnational crime, in which the rampant practice of human trafficking is often not accompanied by optimal protection for victims and effective countermeasures against perpetrators. Based on this, this paper aims to examine how national law regulates the crime of human trafficking, as well as how the Indonesian national legal system provides protection and countermeasures, by considering the factors that cause the crime of human trafficking. The research method employed in this paper is a juridical-normative approach, which examines and analyzes the implementation of legal provisions in legislation concerning human trafficking crimes, utilizing secondary data derived from library research. Therefore, this paper will discuss Law No. 21 of 2007 on the Eradication of the Crime of Trafficking in Persons, which not only regulates criminal sanctions for perpetrators and the protection of victims' rights but also examines how countermeasures are taken against the crime of human trafficking. Consequently, the results of this study demonstrate that Law No. 21 of 2007 has comprehensively regulated the scope of TPPO, encompassing both criminal aspects for perpetrators and protection for victims including restitution, rehabilitation, and confidentiality of identity. Thus, this regulation becomes a concrete instrument for strengthening cooperation with various stakeholders and serves as a key factor in the success of preventing, protecting, and eradicating trafficking in persons as a transnational crime, particularly in Indonesia.